Perspective of the Indonesian Ministry of Religion's Interpretation of the Verse about Gharimin: Examining Online Loans in the Framework of Hifdz al-Mal - Tri Anggraini; Sukiman Sukiman (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the concept of gharimin in Surah At-Taubah verse 60 according to the Qur’anic Exegesis of the Ministry of Religious Affairs of the Republic of Indonesia and to examine its relevance to the phenomenon of online lending from the perspective of hifẓ al-māl (the protection of wealth). This study employed a qualitative approach using library research. Primary data were obtained from Al-Qur’an dan Tafsirnya, published by the Ministry of Religious Affairs of the Republic of Indonesia, while secondary data were derived from Qur’anic exegesis books, scholarly books, journal articles, regulations, and relevant literature on zakat, maqāṣid al-sharī‘ah, and online lending. The data were analyzed using content analysis through a thematic exegesis approach. The findings indicate that gharimin refers to individuals who are burdened by debt and unable to repay it for reasons recognized by Islamic law. The Ministry of Religious Affairs’ interpretation identifies gharimin as eligible recipients of zakat who should be assisted in alleviating economic hardship and preserving their dignity. This concept is relevant to individuals trapped in online lending due to urgent needs, high interest rates and penalties, and limited financial literacy. Within the framework of hifẓ al-māl, zakat functions not only as a means of debt relief but also as a preventive instrument through financial literacy, economic empowerment, social solidarity, and the development of Islamic financing. Therefore, the interpretation of the verse concerning gharimin may serve as a normative foundation for protecting society from the economic consequences of digital debt and for promoting justice, public welfare, and economic resilience.